1988
DOI: 10.1007/bf01342635
|View full text |Cite
|
Sign up to set email alerts
|

Development of hamster circadian rhythms: Role of the maternal suprachiasmatic nucleus

Abstract: During development, the circadian rhythms of rodents become entrained to rhythmicity of the mother. Rhythms in behavior and in neuroendocrine function are regulated by a circadian pacemaker thought to be located within the suprachiasmatic nucleus (SCN) of the hypothalamus. Evidence indicates that this pacemaker begins to function and to be entrained by maternal rhythms before birth. Although the maternal rhythms which mediate prenatal entrainment of the fetal circadian pacemaker have not been identified, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 24 publications
3
65
0
Order By: Relevance
“…1. Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1. Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ablated suprachiasmatic nuclei and subsequently raised in constant dim light are rhythmic with scattered phases (29). However, earlier studies of the ontogeny of Drosophila rhythms have been inconclusive (25,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other species indicate that entrainment during the fetal and early postnatal period is produced by cues derived from the mother (reviewed in Reppert et al, 1989;Takahashi et al, 1989). For example, lesioning of the maternal SCN in the Syrian hamster or rat early in gestation produces litters with asynchronous rhythms (Davis and Gorski, 1988;Reppert and Schwartz, 1986b). Therefore, synchrony shown by the litters in the current study is probably a result of maternal entrainment and not produced by an unknown environmental zeitgeber.…”
Section: Maternal Entrainment In the Siberian Hamstermentioning
confidence: 63%
“…In fact, the potential for entrainment during the postnatal period clearly does exist in the Syrian hamster, as revealed by the synchronizing effects of timed melatonin treatments during the first postnatal week (Grosse et al, 1996). One likely explanation for this species difference may relate to litter size, which is generally smaller for Siberian hamsters (typically 4-5) (Ebling, 1994) than for Syrian hamsters (typically 6-10) (Davis and Gorski, 1988;Davis and Mannion, 1988;Grosse et al, 1996). Honma and colleagues (1987) revealed a litter size effect on the ability of a foster mother to re-entrain the phases of rat pups, in that a greater proportion of pups were synchronized to the phase of the foster mother when the litter size was small than when it was large.…”
Section: Maternal Entrainment During the Preand Postnatal Periodsmentioning
confidence: 99%
See 1 more Smart Citation